2016
DOI: 10.1063/1.4939811
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of low temperature phase MnBi

Abstract: Low temperature phase (LTP) manganese bismuth (MnBi) is a promising rare-earth-free permanent magnet material due to its high intrinsic coercivity and large positive temperature coefficient. While scientists are making progress on fabricating bulk MnBi magnets, engineers have begun considering MnBi magnets for motor applications. Physical properties other than magnetic ones could significantly affect motor design. Here, we report results of our investigation on the mechanical and electrical properties of bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…3) and hardness measurements. The measured hardness values or the α-MnBi phase (66 ± 3 HV) are lower as previously reported 109 ± 15 HV [44], however, the microstructure is not comparable. A hardness value similar to the literature is expected when the ratio o α-MnBi phase increases or nanoindentation would have been perormed directly at the existing α-MnBi phase.…”
Section: Inuence O Pressure and Hpt-deormation On α-Mnbi Ormationcontrasting
confidence: 86%
“…3) and hardness measurements. The measured hardness values or the α-MnBi phase (66 ± 3 HV) are lower as previously reported 109 ± 15 HV [44], however, the microstructure is not comparable. A hardness value similar to the literature is expected when the ratio o α-MnBi phase increases or nanoindentation would have been perormed directly at the existing α-MnBi phase.…”
Section: Inuence O Pressure and Hpt-deormation On α-Mnbi Ormationcontrasting
confidence: 86%
“…The way we obtained this state points to the presence of oxygen vacancy defects during formation of the surface. The enhanced oxygen vacancy diffusion was shown to be the source of the adaptive crystalline structure in amorphous and crystalline forms of Ta 2 O 5 [32], an experimental prototype for the resistive random access memory. Recently [33], also stable polarons were predicted to exist in charged vacancy sites that should affect the carriers mobility.…”
Section: Panel (D)mentioning
confidence: 99%
“…3)). The parental bulk material, especially for the local structure containing the sp 3 -hybridized trimer, is tantalum pentoxide Ta 2 O 5 [32,41]. It is an oxide with a high dielectric constant, and with a reported band gap of ∼ 1 -4 eV.…”
Section: Explanation Of Plaquette Shapes and Contrast Reversalmentioning
confidence: 99%
“…It was found that the temperature stability of the magnetic properties of the NdFeB and Sm 2 Fe 17 N x magnet could be improved by compounding MnBi [6,7].There are many phases in MnBi materials, but only lowtemperature-phase MnBi shows ferromagnetism and its coercivity temperature coefficient is positive. The ferromagnetic low-temperature phase (LTP) MnBi exhibits a hexagonal structure and has uniaxial magnetocrystalline anisotropy at room temperature [8][9][10]. The magnetic properties of MnBi alloy are extremely sensitive to the content of low-temperature MnBi phase.…”
mentioning
confidence: 99%